EL PERIODISTA ANTE LA ENTREVISTA: RUTINAS PROFESIONALES. EL CASO DE CIUDAD VICTORIA, TAMAULIPAS, MÉXICO - Carlos David SANTAMARÍA OCHOA, (Fonseca, Journal of Communication, 2023)
The newspaper interview is sort of use in printed newspapers in Ciudad Victoria Tamaulipas, Mexico. Journalists argue lack of time-space and is to develop this type of work. An analysis of the publications of the largest newspapers in this city dad throws the result that no literary interviews are published, the em-ployee's resource for structuring news and sporadically of reports.